2010
DOI: 10.1021/jm901811v
|View full text |Cite
|
Sign up to set email alerts
|

1-Alkyl-4-phenyl-6-alkoxy-1H-quinazolin-2-ones: A Novel Series of Potent Calcium-Sensing Receptor Antagonists

Abstract: Parathyroid hormone (PTH) is an effective bone anabolic agent. However, only when administered by daily sc injections exposure of short duration is achieved, a prerequisite for an anabolic response. Instead of applying exogenous PTH, mobilization of endogenous stores of the hormone can be envisaged. The secretion of PTH stored in the parathyroid glands is mediated by a calcium sensing receptor (CaSR) a GPCR localized at the cell surface. Antagonists of CaSR (calcilytics) mimic a state of hypocalcaemia and stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 50 publications
4
33
0
Order By: Relevance
“…In addition to a rapid onset of action, calcilytics should have a sufficiently high clearance and a low volume of distribution, allowing a timely clearance of the drug to mimic the pharmacokinetics of injected PTH and thereby reduce the risk of severe adverse effects such as hypercalcemia and the onset of bone resorption. If administered orally, calcilytics might be more convenient than rhPTH and therefore a possible alternative to the prevailing treatment (28).…”
Section: Increasing Endogenous Pth Secretion With Calcilyticsmentioning
confidence: 99%
“…In addition to a rapid onset of action, calcilytics should have a sufficiently high clearance and a low volume of distribution, allowing a timely clearance of the drug to mimic the pharmacokinetics of injected PTH and thereby reduce the risk of severe adverse effects such as hypercalcemia and the onset of bone resorption. If administered orally, calcilytics might be more convenient than rhPTH and therefore a possible alternative to the prevailing treatment (28).…”
Section: Increasing Endogenous Pth Secretion With Calcilyticsmentioning
confidence: 99%
“…However, NPS2143 has unfavorable pharmacokinetic properties in vivo (see section V.D). Later on, several HTS and lead optimization programs have yielded a number of negative allosteric CaSR modulators from various chemical classes: compounds relatively closely related to NPS2143 (Gavai et al, 2005), but also different molecules, such as Calhex 231 (compound II in Table 13) and derivatives thereof (Petrel et al, 2003;Kessler et al, 2006), trisubstituted pyridines/ pyrimidines (compound V in Table 13) (Arey et al, 2005;Yang et al, 2009), benzyloxy analogs (compound IV in Table 13) (Balan et al, 2009), 2-benzylpyrrolidinesubstituted aryloxypropanols (compound VI in Table 13) , 3H-quinazolin-4-ones (compound VII in Table 13) (Shcherbakova et al, 2005), and 4-arylquinazolin-2-ones (compound VIII in Table 13) (Widler et al, 2010) were identified as novel calcilytics, having essentially similar effects on intracellular calcium mobilization and inositol formation in cellular assay systems, some of them also being active in vivo. More compounds having in vivo activity are discussed below.…”
Section: Allosteric Modulators Of the Calcium Sensing Receptor: "Cmentioning
confidence: 99%
“…It is related to proquazone, and was developed at Sandoz in the early 1980s as an analgesic [58][59][60]. Structural modifications of 18 improved the in vitro potency substantially, yielding the most potent calcilytics series known to date in the literature [61]. Key to high antagonistic potency was the replacement of the methoxy by a propargyloxy ether and the switch from the (N1)isopropyl to a benzyl residue (19).…”
Section: Quinazolin-2-ones and Analogsmentioning
confidence: 99%
“…The problem of a slow and protracted absorption phase after oral administration could only be solved by resorting to microemulsion formulations [107]. In striking contrast to the customary ethanol/corn oil formulations for lipophilic drugs, the use of microemulsions produced high-and short-lasting exposure levels as desired, especially in dogs where generally almost perfect PK/pharmacody-pharmacody-harmacodynamic correlations were observed [61]. However, structural modifications strongly influenced the PK profiles of the individual derivatives, and in some cases the results were also highly species-dependent.…”
Section: Quinazolin-2-ones and Analogsmentioning
confidence: 99%